Advancing quantitative clinical pharmacology competencies in Francophone Africa through an on-line learning framework - Nour Chtiba; Sihem Ait-Oudhia; Sonia Khier; Anna Chan Kwong; Innocent G. Asiimwe; Florence Gattacceca; Miriam Razgallah Khrouf; Paul Baverel; Celine Sarr; Anaïs Glatard; Julie Bertrand; Nada Abla; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2026)

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Doublesex is essential for masculinization but not feminization in Lygus hesperus - J. Joe Hull; Chan C. Heu; Roni J. Gross; Dannialle M. LeRoy; Inana X. Schutze; Daniel Langhorst; Jeffrey A. Fabrick; Colin S. Brent (Insect Biochemistry and Molecular Biology, 2024)

β-tubulin functions in spermatogenesis in Lygus hesperus Knight - Chan C. Heu; Kevin P. Le; Roni J. Gross; Inana X. Schutze; Dannialle M. LeRoy; Daniel Langhorst; Colin S. Brent; Jeffrey A. Fabrick; J. Joe Hull (Journal of Insect Physiology, 2024)

The Critically Endangered Hainan Gibbon (Nomascus hainanus) Population Increases but not at the Maximum Possible Rate - Guioqi Liu; Xueli Lu; Zhao Liu; Zhi Xie; Xuming Qi; Jiang Zhou; Xiaojiang Hong; Yanni Mo; Bosco P. L. Chan; Colin A. Chapman; Zhigang Jiang (International Journal of Primatology, 2022)
With the ongoing global biodiversity crisis in the Anthropocene, it is critical to understand how to save endangered species to “bend the curve” of biodiversity decline. The Hainan gibbon ( Nomascus hainanus ) is a Critically Endangered species that is endemic to Hainan Island. We performed two synchronized total count surveys in Hainan Tropic Rain Forest National Park in November and December of 2020 and 2021 by locating gibbon groups from their morning calls and conducting detailed counts in all potential habitat fragments. We compared our findings with existing data to model the population trend, and analyzed the potential and realized reproductive potentials. We found 5 groups with a total of 33 gibbons in 2020 and 35 in 2021, including 4 and 6 solitary individuals respectively. This is an increase of 169% since 2003, when there were 13 individuals with 2 groups and 2 solitary individuals. Logistic and linear curves fitted the 2003-2021 population census data equally well. Although the population is growing, it has not realized its full reproductive potential (when all adult females give births at 24-month intervals), suggesting that external factors like available habitat, as well as nutritional, physiological, and behavioral factors may be limiting the population. The gibbon’s recovery demonstrates that establishing a nature reserve with regular patrols, banning logging, curbing poaching, and environmental education have been effective. Because the Hainan gibbon population is still extremely small, carefully planned conservation actions, including an ambitious forest restoration program, will be needed to ensure the species’ continued survival.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Tropical and subtropical Asia's valued tree species under threat - Hannes Gaisberger; Tobias Fremout; Chris J. Kettle; Barbara Vinceti; Della Kemalasari; Tania Kanchanarak; Evert Thomas; Josep M. Serra‐Diaz; Jens‐Christian Svenning; Ferry Slik; Wichan Eiadthong; Kandasamy Palanisamy; et al. (Conservation Biology, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration.

Donation of discarded ocular tissue in patients undergoing SMILE laser refractive surgery: developing appropriate guidelines - Mona Ghabcha; Gerard Sutton; Con Petsoglou; Jane Treloggen; Michael Lawless; Colin Chan; Chris Hodge (Cell and Tissue Banking, 2020)

Nonnative Species in British Columbia Eelgrass Beds Spread via Shellfish Aquaculture and Stay for the Mild Climate - Megan E. Mach; Colin D. Levings; Kai M. A. Chan (Estuaries and Coasts, 2017)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

A Rifapentine-Containing Inhaled Triple Antibiotic Formulation for Rapid Treatment of Tubercular Infection - John Gar Yan Chan; Anneliese S. Tyne; Angel Pang; Hak-Kim Chan; Paul M. Young; Warwick J. Britton; Colin C. Duke; Daniela Traini (Pharmaceutical Research, 2014)

An Atlantic infaunal engineer is established in the Northeast Pacific: Clymenella torquata (Polychaeta: Maldanidae) on the British Columbia and Washington Coasts - Megan E. Mach; Colin D. Levings; P. Sean McDonald; Kai M. A. Chan (Biological Invasions, 2012)

Scale-up of Adhesive Transdermal Drug Delivery Systems - Glenn A. Van Buskirk; Mario A. González; Vinod P. Shah; Scott Barnhardt; Colin Barrett; Stephen Berge; Gary Cleary; Keith Chan; Gordon Flynn; Thomas Foster; Robert Gale; Raymond Garrison; et al. (Pharmaceutical Research, 1997)